Impact of Digital Divide on The Growth and Development of Small and Medium Enterprises in Kabale District: A Case Study of Kigezi Private Sector Promotion Centre Limited. - Kembabazi, Evaline (Kabale University, 2024)
The general objective of the study was to assess the impact of the Digital divide on the growth and development of SMES at Kigezi Private Sector Promotion Centre Limited- Kabale District. It is set to identify factors for the digital divide in SME development at Kigezi Private Sector Promotion Centre Limited, establish the challenges faced in minimizing the digital divide among people and suggest the strategies and make recommendations in place to address the challenges of the digital divide at Kigezi Private Sector promotion Centre Limited. The study used a cross-sectional survey design since this allows one to conduct the study within a short period of me as opposed to a longitudinal approach. A cross-sectional survey design was adopted to take a snapshot of events as they exist there and then. The focus was on staff and clients of the Kigezi Private Sector. The target population of the study was 70 respondents. The sample size of the study was composed of 54 respondents, derived from an access population of 70 participants. From the findings, among roles promoting effective reporting to government agencies was ranked first followed by proper planning and prioritization of needs, Monitoring and evaluation. proper communication among administrative staff hence electronic records management was important at Kigezi Private Sector Promotion Centre. It was also found that the Misplacement of digitally generated files followed by Failure to provide some services like computer training, refresher pieces of training, Attacks from viruses and Trojans, creates overall poor service delivery of the records facility, Inadequate supply of computers, Installation of outdated records management programmes like windows XP was at and to a small extent, respondents identified Client dissatisfaction as in accounting for District materials. This implies that there were many challenges faced due to electronic records of records personnel in the Kigezi Private Sector Promotion Centre. There was a need for the centre management to adjust monitoring advances in the records sector by the centre records teams and the Ministry of records. It was also recommended that Kigezi Private Sector Promotion Centre management should look for financial resources to restructure the records facility ranging from expansion of the centre to updating services available so that updated services are availed to clients at all times.